2015
DOI: 10.1016/j.apcata.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

In situ magnetic resonance imaging study of the impregnation of γ-alumina pellets

Abstract: a b s t r a c tIn petroleum refining, ␥-alumina is used as a solid support of molybdenum nickel/cobalt promoted catalysts for the hydrotreatment processes, such as hydrodesulfurization. The ever decreasing norms for the sulfur content in gasoline require better and more efficient catalysis, prompting extensive research on the materials and the factors influencing the activity, selectivity and stability of the catalytic processes. In the present study, Magnetic Resonance Imaging Single Point Imaging is tested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Typical impregnation times in the range of a few minutes to 1 or 2 h are employed for alumina in industry. , Residence times (corresponding to the experimental times or the time spent by the nickel solution inside the reactor) of between 10 and 940 min have been chosen to monitor the dynamics of the nickel and proton adsorption. Greater residence times have not been performed to avoid alumina dissolution. , The impregnation experiments are conducted at a temperature of 25 °C since alumina extrudates are typically impregnated under ambient conditions in industry.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Typical impregnation times in the range of a few minutes to 1 or 2 h are employed for alumina in industry. , Residence times (corresponding to the experimental times or the time spent by the nickel solution inside the reactor) of between 10 and 940 min have been chosen to monitor the dynamics of the nickel and proton adsorption. Greater residence times have not been performed to avoid alumina dissolution. , The impregnation experiments are conducted at a temperature of 25 °C since alumina extrudates are typically impregnated under ambient conditions in industry.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, many researchers studied the adsorption of cationic metal species, including nickel, from aqueous solutions on alumina structures. Among these researchers, some evaluated the distribution of the metallic species inside the solids at different aging times during impregnation experiments of alumina using magnetic resonance imaging or MRI, ,, Raman spectroscopy, , electron microprobe analysis, and most recently LIBS imaging. , They emphasized the effect of the metal concentration and the presence of additives in the impregnation solution on the metal distribution profiles inside the alumina solids. Others investigated the metal adsorption efficiency at equilibrium by monitoring the liquid phase in contact with alumina solids during batch experiments (mostly using inductively coupled plasma–optical emission spectroscopy or ICP–OES, atomic absorption spectroscopy or AAS, and UV/vis absorbance techniques). ,,, These studies showed that the operating conditions (initial pH, initial metal concentration, adsorbent dosage, contact time, and temperature) impact the removal of metal species.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations